Synthesis and Characterization of Phenylalanine Nanotubes as Green pH‐Responsive Drug Nanocarriers. Issue 40 (27th October 2020) - Rohani Shirvan, Anahita; Hemmatinejad, Nahid; Bahrami, Seyed Hajir; Bashari, Azadeh
Abstract: The present study is aiming to investigate the potential of phenylalanine amino acid nanotubes (PhNTs) synthesized by a self‐assembly process as an efficient and pH‐responsive green drug nanocarrier for the treatment of oral disease. Phenylalanine was used for the preparation of solutions with three different concentrations (0.1, 0.5 and 2.5 mg/ml). Scanning electron microscopy (SEM) and Field emission scanning electron microscopy (FESEM) images showed that low and high concentrations of phenylalanine solution creates nanospheres and nanowires, respectively rather than tubular‐shaped nanostructures. In contrast, phenylalanine nanotubes were synthesized by medium concentration (0.5 mg/ml). The tubular shape and nanoscale diameter of the synthesized PhNTs were characterized by FESEM, Transmission Electron microscopy (TEM), Dynamic Light Scattering (DLS) and Fourier Transform Infrared Spectroscopy (FTIR). These characterization tests confirmed the synthesis of PhNTs with a tubular shape and nanoscale diameter. In the second stage, metronidazole was loaded into the phenylalanine‐based nanostructures as an effective drug for oral disorders. The results indicated that nanospheres and nanowires show drug loading efficiency of 49 % and 58 %, respectively, after 48 h of incubation time. Whereas, the drug loading efficiency for nanotubes was 91 %. The results from the FTIR analysis and UV‐vis spectroscopy verified the presence of metronidazole into the hollow structure of PhNT. While a burst drug release was observed for nanospheres and nanowires, PhNTs showed a well‐controlled release of metronidazole up to 95 % at oral pH, which is best fitted to the Weibull model. Subsequently, the cell viability of phenylalanine‐based nanostructures was assessed by MTT test on L929 fibroblast cell line. Abstract : Phenylalanine amino acids are introduced as a new bio‐source for the fabrication of nanotubes with pH‐responsive properties and high drug loading capacity. An optimized concentration of phenylalanine amino acid solution was used for the synthesis of nanotubes and loaded with metronidazole as an antibiotic agent. Facile synthesis and cost‐effective process, excellent cell biocompatibility, efficient drug encapsulation and sustained pH‐responsive releasing properties make phenylalanine nanotubes promising nanocarriers for the controlled release of drugs, in particular for oral drug administration.